INVESTIGATING VEGETATION COVER AND SAND DUNES EVOLUTION IN RUMAITHA DISTRICT USING DIGITAL INDICATORS FOR THE YEARS (2000 – 2023) (CAHIERS MAGELLANES-NS, 2024)
The study utilized spectral indicators such as NDVI and NDSDI, along with satellite imagery interpretation, to detect changes in vegetation cover and sand dunes areas in the Rumaitha district between 2000 and 2023.  American satellites, Landsat 4 for 2000 and Landsat 9 for 2023, with a spatial resolution of 30m, were employed for data collection to compare the changes that occurred to the land cover during that period. Digital data from satellite imagery were analyzed using Erdas 2016 software, and final outputs were generated using ArcMap 10.8 to create digital maps. The research employed descriptive and analytical approaches, analyzing climate data, satellite imagery, and administrative maps. Results revealed that barren, uncultivated lands constituted 66.24% of the district in 2000, decreasing to 53.45% in 2023.  Similarly, sand dune areas decreased from 77.2% in 2000 to 66.6% in 2023. These findings suggest a positive trend toward increased vegetation cover in the study area, at the expense of barren lands and sand dunes.